Pre- and postpartum supplementation strategies on the performance and metabolic status of grazing beef cows - Moreno, Deilen Sotelo; Ortega, Román Maza; Paulino, Mário Fonseca; Rennó, Luciana Navajas; Detmann, Edenio (Pesquisa Agropecuaria Brasileira, 2024)
The objective of this work was to evaluate the effect of energy-protein supplementation in pre- and postpartum periods on the productive and metabolic responses of grazing beef cows on tropical pasture. A group of 48 multiparous Nellore cows, with an initial gestation period of 6.4 months, body weight (BW) of 514.9 kg, and body condition score (BCS) of 5.4, was distributed in a completely randomized design, in a 2×2 factorial arrangement. The evaluated treatments were: UNS-UNS, unsupplemented during prepartum and postpartum; UNS-SUP, unsupplemented during prepartum and supplemented during postpartum; SUP-UNS, supplemented during prepartum and unsupplemented during postpartum; and SUP-SUP, supplemented during pre- and postpartum. The energy-protein supplement was offered at an amount of 1.5 kg per animal per day. Prepartum supplementation increased average daily gain and BCS at calving. Prepartum supplementation reduced non-esterified fatty acids (NEFA) and increased serum concentrations of total proteins and globulins during postpartum. Postpartum supplementation increased the BCS of cows and BW of calves at the end of the experiment. Postpartum supplementation increased blood concentrations of progesterone, while NEFA decreased. Supplementation with 1.5 kg per day of the energy-protein supplement during the last 84 days of gestation improves productive performance and metabolic status during the pre- and postpartum periods of grazing cows.
Keywords: Nellore cows; periparturient period; ruminant nutrition; tropical forage